Plant host and soil origin influence fungal and bacterial assemblages in the roots of woody plants. Issue 13 (July 2014) - Bonito, Gregory; Reynolds, Hannah; Robeson, Michael S.; Nelson, Jessica; Hodkinson, Brendan P.; Tuskan, Gerald; Schadt, Christopher W.; Vilgalys, Rytas
Abstract Microbial communities in plant roots provide critical links between above‐ and belowground processes in terrestrial ecosystems. Variation in root communities has been attributed to plant host effects and microbial host preferences, as well as to factors pertaining to soil conditions, microbial biogeography and the presence of viable microbial propagules. To address hypotheses regarding the influence of plant host and soil biogeography on root fungal and bacterial communities, we designed a trap‐plant bioassay experiment. Replicate Populus, Quercus and Pinus plants were grown in three soils originating from alternate field sites. Fungal and bacterial community profiles in the root of each replicate were assessed through multiplex 454 amplicon sequencing of four loci (i.e., 16S, SSU, ITS, LSU rDNA). Soil origin had a larger effect on fungal community composition than did host species, but the opposite was true for bacterial communities. Populus hosted the highest diversity of rhizospheric fungi and bacteria. Root communities on Quercus and Pinus were more similar to each other than to Populus. Overall, fungal root symbionts appear to be more constrained by dispersal and biogeography than by host availability.